Identification of the demographic and clinical factors in determining the effectiveness of robotic-assisted radical prostatectomy - Mohd Osman, Balkish; Md Ghani, Nor Azura; Ani, Roziah; Md Ghani, Khairul Asri (IEEE (IEEE Xplore), 2013)
Prostate cancer is a disease facing the male which has shown a significant increase worldwide and is ranked sixth globally. In Malaysia, prostate cancer is ranked sixth as the leading cause of death among male cancer patients. The breakthrough in technology has shown that the robotic-assisted radical prostatectomy (RARP) is a treatment of choice compared to the traditional open surgery. This study focuses on the effectiveness of the RARP as this procedure benefits the patients including faster return of urinary continence, erectile function and cancer control. Even though studies have shown that the RARP has resulted in quick recovery and better functional outcome, yet post surgeries by RARP have shown patients have a full return of urinary continence while a few others do not. This study was conducted to investigate the association among the potential risk factors and the effectiveness of the RARP and the association with the demographic as confounding factors. This study used the secondary data obtained from the Urology Department at Hospital Kuala Lumpur. The summary and descriptive statistics were performed to explain the demographic profile of the patients. The chi-square test was used to determine the association among the potential risk factors. The result indicates that all potential risk factors are not significantly associated with the effectiveness of the RARP except for detection of cancer. In addition it was found that Indians with margin location at apex has a chance of grade 2 effectiveness of RARP.